Electrostatic enhancement of light emitted by semiconductor quantum well. (September 2015) - Krokhin, A; Neogi, A; Llopis, A; Mahat, M; Gumen, L; Pereira, S; Watson, I
Abstract: Carrier dynamics in metal-semiconductor structures is driven by electrodynamic coupling of carriers to the evanescent field of surface plasmons. Useful modifications in electron and hole dynamics due to presence of metallic inclusions show promise for applications from light emitters to communications. However, this picture does not include contributions from electrostatics. We propose here an electrostatic mechanism for enhancement of light radiated from semiconductor emitter which is comparable in effect to plasmonic mechanism. Arising from Coulomb attraction of e-h pairs to their electrostatic images in metallic nanoparticles, this mechanism produces large carrier concentrations near the nanoparticle. A strong inhomogeneity in the carrier distribution and an increase in the internal quantum efficiency are predicted. In our experiments, this manifests as emission enhancement in InGaN quantum well (QW) radiating in the near-UV region. This fundamental mechanism provides a new perspective for improving the efficiency of broadband light emitters.